197k views
3 votes
Simplify and solve this equation: 4m+9+5m-12=42

User Velimir
by
4.4k points

2 Answers

2 votes
You first must add together the same values
So
4m+5m=9m
+9+-12 =-3
So you have
9m-3=42
Then you put the -3 on the other side you you add 3 in to both sides so now you have
9m =45
And then divide 45 divided by 9 = 5
So the answer is m=5
User MatanGold
by
5.3k points
4 votes
First you combine like variables
9m - 3 = 42
then add both sides
9m = 45
then divide whats left
m = 5
User Saurabh Solanki
by
5.4k points